Zastosowanie ontologii w inżynierii wymagań - Sobczak, Andrzej (Application of ontology at requirements engineering, 2006)
The use of the natural language in the process of requirements documentation in many instances makes it impossible to obtain a correct (i.e. unequivocal and coherent) list of requirements. The obstacle to obtaining such a list lies in the fact that the same text is understood in different ways by different stakeholders. The article focus on new technique for requirements representation which author calls: “semi-FormAl Representation of the requirements using Ontology-based group memory System".
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 56-64